Novel Carbon Dots Derived from Glycyrrhizae Radix et Rhizoma and Their Anti-Gastric Ulcer Effect - Liu, Yuhan; Zhang, Meiling; Cheng, Jinjun; Zhang, Yue; Kong, Hui; Zhao, Yan; Qu, Huihua (Molecules (Basel, Switzerland), 2021)
Glycyrrhizae Radix et Rhizoma (GRR) is one of the commonly used traditional Chinese medicines in clinical practice, which has been applied to treat digestive system diseases for hundreds of years. GRR is preferred for anti-gastric ulcer, however, the main active compounds are still unknown. In this study, GRR was used as precursor to synthesize carbon dots (CDs) by a environment-friendly one-step pyrolysis process. GRR-CDs were characterized by using transmission electron microscopy, high-resolution TEM, fourier transform infrared, ultraviolet-visible and fluorescence spectroscopy, X-ray photoelectron spectroscopy, X-ray diffraction and high-performance liquid chromatography. In addition, cellular toxicity of GRR-CDs was studied by using CCK-8 in RAW264.7 cells, and the anti-gastric ulcer activity was evaluated and confirmed using mice model of acute alcoholic gastric ulcer. The experiment confirmed that GRR-CDs were the spherical structure with a large number of active groups on the surface and their particle size ranged from 2 to 10 nm. GRR-CDs had no toxicity to RAW264.7 cells at concentration of 19.5 to 5000 μg/mL and could reduce the oxidative damage of gastric mucosa and tissues caused by alcohol, as demonstrated by restoring expression of malondialdehyde, superoxide dismutase and nitric oxide in serum and tissue of mice. The results indicated the explicit anti-ulcer activity of GRR-CDs, which provided a new insights for the research on effective material basis of GRR.